2021
DOI: 10.31014/aior.1994.04.04.190
|View full text |Cite
|
Sign up to set email alerts
|

Sentul Fruit (Sandoricum koetjape) Peel as Anti-Inflammation for Gingivitis after Scaling

Abstract: Various herbs are used as analgesic, anti-inflammatory, anti-bacterial, anti-fungal, expectorant, anti-plaque and odorant. Sentul is an edible fruit and is also used in traditional medicinal herbs which can treat diarrhea, relieve fever, and as an anthelmintic. Sentul bark methanol extract can inhibit the growth of fungus Candida albican by 39.65%. In addition, the ethyl acetate extract of the sentul leaves also has anti-bacterial activity. The aim of this study is to determine the effect of fractionation with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The research results on Sentul fruit peel extract from several phytochemical compounds, flavonoid compounds, saponins and tannins are aromatic hydroxyl groups that act as antibacterial. 10 This study aimed to determine the inhibitory ability of Sentul fruit peel extract (Sandoricum koetjape) against Streptococcus mutans and Staphylococcus The results showed that sentul extract was able to inhibit the growth of S. mutans and S. aureus bacteria as seen from the formation of a clear zone. This indicates that the sentul extract has antibacterial ability to the concentration of the extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results on Sentul fruit peel extract from several phytochemical compounds, flavonoid compounds, saponins and tannins are aromatic hydroxyl groups that act as antibacterial. 10 This study aimed to determine the inhibitory ability of Sentul fruit peel extract (Sandoricum koetjape) against Streptococcus mutans and Staphylococcus The results showed that sentul extract was able to inhibit the growth of S. mutans and S. aureus bacteria as seen from the formation of a clear zone. This indicates that the sentul extract has antibacterial ability to the concentration of the extract.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of ethanol solvent and aquades fraction was based on previous research where the sentul ethanol extract of the aqua fraction gave the highest levels of flavonoid compounds, saponins and tannins with flavonoid levels of 11476.16 mg/100g QE, tannins 88.605 mg/g and 6.862 mg/g. 10 Lower concentration certainly contains fewer antibacterial compounds. This is in accordance with Rahmawati et al 11 that the greater the interaction concentration of a given extract, the greater the diameter of the inhibition formed, because the more bioactive components contained in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Sandoricum koetjape leaf has xanthine oxidase inhibitory and antioxidant properties [11]. After scaling, an ethanol extract of Sandoricum koetjape fruit peel has anti-gingival inflammation properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7 cells from humans with breast cancer are cytotoxic to gallic acid and caffeic acid, inducing apoptosis [15]. Koetjapic acid, a phenolic acid found in the bark of Sandoricum koetjape, has anticarcinogenic properties [12]. Katonic acid, another phenolic acid derived from Sandoricum koetjape, was found to be cytotoxic to ten cancer cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf of S. koetjape has xanthine oxidase inhibitory activity and antioxidant activity (Hamzah et al 2020). S. koetjape fruit peel ethanol extract has anti-inflammation properties for gingivitis after scaling (Wirata et al 2021). In vitro studies showed the pharmacological potential of S. koetjape extract, including antioxidant, antibacterial, anticancer, antitumor, and insecticide activities (Wijaya 2022).…”
Section: Introductionmentioning
confidence: 99%